Leadership in English Education - Titim Eliawati; Muhammad Naufal (Journal MELT (Medium for English Language Teaching), 2022)
The Covid-19 pandemic has changed the way people live, including in Indonesia. Schools to make changes to the learning system so that teachers and students feel comfortable in the classroom and at home in carrying out learning activities at school. The school leadership was not spared from this problem. School leaders must quickly make the right decisions about what must be done in response to the changes that have occurred due to this pandemic. The purpose of this study is to collect various data to then be analyzed and reviewed regarding the decisions taken by the principal so that this abnormal condition becomes normal by conditioning several things at school. The research method used is literature review by reviewing various library sources which are the results of various studies. The result of this study is the principal's leadership in increasing teacher creativity and innovation, which occurs because the principal is always proactive in dealing with various contextual problems in schools. The principal must also be ready to make strategic decisions so that school stakeholders do not have to wait too long in carrying out the next activities in the school so that the learning process continues.